TRTH-06. CHILDREN’S BRAIN TUMOUR DRUG DELIVERY CONSORTIUM - Rahman, Ruman (Neuro Oncol, 2017)
INTRODUCTION: Whilst there is an urgent need to expedite the development of new or repurposed drugs for children’s cancer, the additional challenge in the developing brain is to ensure the drug is delivered to the tumour at therapeutic and non toxic concentrations for sufficient duration to achieve the biological effect. This is the necessary focus for personalised medicine agendas in children’s brain tumours as they account for over 20% of childhood cancer and differ significantly in their biological characteristics from their adult counterparts. METHODS: The authors took part in an international CNS drug delivery London workshop funded by the charity Children with Cancer UK (CwC) in February 2016 where different experimental techniques aimed at optimising CNS drug delivery in children’s brain tumours were presented and discussed. RESULTS: The workshop was reported (1) and promoted through e-cancer (2). We were encouraged to develop a proposal, to establish an international research consortium to raise awareness and promote collaboration in the field. This is now to be funded for two years by Children with Cancer. The Children’s Brain Tumour Drug Delivery Consortium will organise and host discussions between an international, multi-disciplinary network of clinicians and researchers within pharma and academia as well as a range of funders and stakeholders. This Consortium seeks to strengthen collaborative developments by working closely with the international children’s brain tumour community. CONCLUSION: We present this abstract to the SNO Pediatric conference to launch this initiative in North America and invite collaborators to promote this research priority for children across the world and to consider joining the consortium, which will be presented at the conference. 1. NAILOR,A, WALKER,DA and ET AL, 2016. Highlights of Children with Cancer UK’s Workshop on Drug Delivery in Paediatric Brain Tumours eCancer. 10, 630. 2. http://ecancer.org/conference/831-drug-delivery-in-paediatric-brain-tumours.php